Habitat use of the amphidromous catfish Genidens barbus: first insights at its southern distribution limit - Avigliano, Esteban (2021)
Fil: Avigliano, Esteban. Universidad de Buenos Aires, Facultad de Ciencias Veterinarias. Buenos Aires, Argentina.